Fatherhood crisis: Drawing inspiration from hunhu/ubuntu and Saint Joseph - Rutsviga, Alois (HTS teologiese studies, 2024)
The article seeks to purvey a moral philosophical foundation to the apostolic letter. The apostolic letter speaks pointedly of the fatherhood crisis as an issue that needs moral philosophical atrention. The research will use two methods: the philosophical (content) analysis and applied ethical theories. Philosophical analysis is a general term for techniques typically used by philosophers in the analytic tradition that involve breaking down philosophical issues in order to bring clarity, consistence, and coherence. The method is used to analyse concepts like parenthood, fatherhood and shepherdship. Applied ethics is a philosophical examination, from a moral point of view, of particular issues in private and public life which are matters of judgement. However, the punch line, ‘Children today often seem orphans, lacking fathers’, is a direct moral challenge that calls for the application of the ethical theory of hunhu/ubuntu because love is hunhu/ubuntu’s character, nature and responsibility. From hunhu/ubuntu’s view point, I argue that one must acquire personhood primarily first in order to be a father. In hunhu/ubuntu, personhood and fatherhood are dynamic concepts; morally achieved and acquired. Hunhu/ubuntu is not asking that we replace God as the author of our being, but rather that our being as persons in the world is substantially of our own making. As such, we have a victory to win, and the path to that victory lies in the part of our lived morality (hunhu/ubuntu). God created us, but we must mould ourselves into the persons that God wants us to be.Contribution: The intention of this article is to encourage the 21st century generation to be good persons and hence be responsible fathers through drawing moral support and inspiration from hunhu/ubuntu and Saint Joseph.